“The sacred hill”. Imaginaries and spatial practices around the Uritorco hill (Córdoba) (Huellas, 2023)
Uritorco hill, at 1950 meters above sea level, is the highest massif in the Sierras Chicas range in Córdoba. Since the 1980s, a series of narratives around the hill began to emerge, which turned into a framework of sacredness where ancestral indigenous legends, stories about UFO and intra and extraterrestrial alien appearance, and new age, esoteric and mystical discourses that underwrite its sacredness are interwoven. In this article we focus on understanding how the Uritorco hill was constructed as a representative of this type of discourse, that is, how the geographical object was conceived (and is still conceived) as a sacred space, placing the analysis in the spatial perspective. In this sense, the focus will be placed upon two key dimensions that shape the cultural geographical approach: on the one hand, the geographical imaginaries powered by present spatial discourses and, on the other hand, the concrete practices that subjects display and that are motorized by those imaginaries about the place.
Keywords: sacredness; sacred space; hill; spatial practices